Role of oxidized low density lipoprotein in atherogenesis. - Witztum, J L (1991)
Evidence to support an important role of oxidative modification in mediating the atherogenicity of LDL continues to grow. New hypotheses suggest mechanisms by which Ox-LDL or products of Ox-LDL can affect many components of the atherogenic process, including vasomotor properties and thrombosis, as well as lesion initiation and progression itself. These ideas suggest new approaches, that in combination with lowering of plasma cholesterol, could lead to the prevention of atherosclerosis and its complications.